Tanggung Jawab Pelaku Usaha Terhadap Kerugian Konsumen Akibat Produk Cacat - Oktaviani, Windi Eka (Fakultas Hukum Universitas Islam Jakarta, 2016)
Responsibilities of the manufacturer of the defective product in terms of consumer protection, investigate the implementation of producer responsibility with regard to consumer lawsuit over defective products. The purpose of this research was to determine how the legal effort to prevent consumers are not harmed as a result of the items used in a state of disrepair and how the responsibility of businesses to provide compensation for damage to goods. By using the method of normative legal research concluded that legal efforts to prevent the consumer is not harmed as a result of the items used in a state of disrepair through the fulfillment of the obligations businessmen to carry out business activities in good faith. Businesses must provide correct information, clear and honest about the condition and guarantee of goods based on quality standards as well as to explain the use, repairs and maintenance. Business actors are required to give consumers a chance to test, and/or try a particular item and give a guarantee and/or guarantees on goods manufactured and/or traded. Responsibility of business operators provide compensation for damage to goods that harm consumers can be either a refund or replacement of goods similar or equivalent value, or the health care and the provision of compensation in accordance with the provisions of the legislation in force. As stipulated in Article 19 of the UUPK, makes the manufacturer cannot deny its responsibility in the event of a lawsuit over defective products. The obstacles that arise in the implementation of producer responsibility on the basis of consumer lawsuit over defective products is the length of time of completion in terms of not going peace of proof in consumer dispute resolution between the provisions UUPK. ABSTRAK Tanggung Jawab produsen terhadap produk cacat ditinjau dari perlindungan konsumen, mengetahui pelaksanaan tanggung jawab produsen berkaitan dengan gugatan konsumen atas produk cacat. Tujuan dilakukannya penelitian ini adalah untuk mengetahui bagaimana upaya hukum untuk mencegah konsumen tidak dirugikan akibat barang yang digunakan dalam keadaan rusak dan tanggung jawab pelaku usaha memberikan ganti rugi atas kerusakan barang. Penelitian hukum normatif disimpulkan bahwa upaya hukum untuk mencegah konsumen tidak dirugikan akibat barang yang digunakan dalam keadaan rusak melalui pemenuhan kewajiban pelaku usaha untuk melaksanakan kegiatan usaha dengan beritikad baik. Pelaku usaha harus memberikan informasi yang benar, jelas dan jujur mengenai kondisi dan jaminan barang berdasarkan standar mutu serta memberi penjelasan penggunaan, perbaikan dan pemeliharaan. Pelaku usaha diwajibkan untuk memberi kesempatan kepada konsumen untuk menguji, dan/atau mencoba barang tertentu serta memberi jaminan dan/atau garansi atas barang yang dibuat dan/atau yang diperdagangkan. Tanggung jawab pelaku usaha memberikan ganti rugi atas kerusakan barang yang merugikan konsumen dapat berupa pengembalian uang atau penggantian barang yang sejenis atau setara nilainya, atau perawatan kesehatan dan pemberian santunan yang sesuai dengan ketentuan peraturan perundang-undangan yang berlaku. sebagaimana diatur dalam ketentuan Pasal 19 UUPK, menjadikan produsen tidak bisa mengingkari tanggung jawabnya dalam hal terdapat gugatan atas produk cacat. Kendala-kendala yang muncul dalam pelaksanaan tanggung jawab produsen atas dasar gugatan konsumen atas produk cacat adalah lamanya waktu penyelesaian dalam hal tidak terjadi perdamaian pembuktian dalam penyelesaian sengketa konsumen antara ketentuan UUPK.